2006
DOI: 10.14219/jada.archive.2006.0054
|View full text |Cite
|
Sign up to set email alerts
|

In vitro microtensile bond strength of four adhesives tested at the gingival and pulpal walls of Class II restorations

Abstract: Background-The authors compared the microtensile bond strength of teeth restored with four adhesives at the gingival and pulpal cavity walls of Class II resin-based composite restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
6
1
2
Order By: Relevance
“…Micro-tensile bond strength to enamel[36] and dentin[353738] and micro-shear[28] bond strengths to dentin varied depending on the location of substrate similar to that of macro-tests. Majority of the authors concluded that results depended on the type of adhesive system.…”
Section: Variables Influencing Micro-bond Strength Test Resultsmentioning
confidence: 99%
“…Micro-tensile bond strength to enamel[36] and dentin[353738] and micro-shear[28] bond strengths to dentin varied depending on the location of substrate similar to that of macro-tests. Majority of the authors concluded that results depended on the type of adhesive system.…”
Section: Variables Influencing Micro-bond Strength Test Resultsmentioning
confidence: 99%
“…[22] On the other hand, ASB total etch bond has previously been used in many comparative studies. [2324] Self-etch adhesives and composites may offer some advantages over the use of total etch adhesives. Self-etch adhesives have weak acids in their primer composition, which results in less change in the dentinal wall structure than with the strong acids of total etch systems.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to evaluate the impact of contact time of the primer on the tooth substrate, additional priming times of 30, 60, and 120 seconds were added after normal application duration, but these did not influence MTBS, as measured on the gingival wall of Class II cavities. 69 In another study 70 from the same authors, it was concluded that MTBS values were not influenced by location (pulpal or gingival wall) for the various adhesives tested. However, the three-step total-etch, water-based adhesive and the two-step acetone-based prime and bond systems produced lower values than the two-step waterbased self-etch and two-step total-etch ethanol-based systems.…”
Section: Microtensile and Shear Testsmentioning
confidence: 96%
“…Incremental and centripetal (layering from depth to surface) techniques showed a reduction in microleakage in cervical dentin compared to bulk-filling in numerous studies [69][70][71][72][73] ; however, the use of various restorative techniques had no influence on microleakage at enamel margins. 74,75 Overall, less microleakage was observed at enamel margins compared to cervical dentin.…”
Section: Comparison Of Restorative and Layering Techniquesmentioning
confidence: 99%
See 1 more Smart Citation